2002
DOI: 10.2337/diacare.25.8.1346
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Autoimmunity in Children and Adolescents With Type 1 Diabetes

Abstract: OBJECTIVE -To investigate thyroid autoimmunity in a very large nationwide cohort of children and adolescents with type 1 diabetes.RESEARCH DESIGN AND METHODS -Data were analyzed from 17,749 patients with type 1 diabetes aged 0.1-20 years who were treated in 118 pediatric diabetes centers in Germany and Austria. Antibodies to thyroglobulin (anti-TG) and thyroperoxidase (anti-TPO) were measured and documented at least once in 7,097 patients. A total of 49.5% of these patients were boys, the mean age was 12.4 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
162
9
24

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(225 citation statements)
references
References 19 publications
30
162
9
24
Order By: Relevance
“…As in previous reports, girls and children at older age are more likely to have thyroid autoantibodies [1,13,26,27,29,33]. This correlates with reports involving adults wherein women with type 1 diabetes are more prone to autoimmune thyroiditis than men [34].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…As in previous reports, girls and children at older age are more likely to have thyroid autoantibodies [1,13,26,27,29,33]. This correlates with reports involving adults wherein women with type 1 diabetes are more prone to autoimmune thyroiditis than men [34].…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, only few children are diagnosed with AITD at the onset of type 1 diabetes [23,26,31], while the risk of AITD increases during follow-up of patients with type 1 diabetes. It has been estimated that 10-33% of adult patients with long-term type 1 diabetes have been diagnosed with clinical AITD [29,[32][33][34] and in patients followed from diagnosis TPOAb predict development of future thyroid disease [35]. It is important to diagnose childhood clinical hypothyroidism due to AITD as it has an impact on growth, intellectual development and metabolic control.…”
Section: Discussionmentioning
confidence: 99%
“…Radetti et al (77) found high levels of TPOAb in nearly 24% of overweight or obese children. This prevalence is similar to that observed in children with type 1 diabetes mellitus (21.6%) (123) and outnumbers current epidemiologic data in iodine-sufficient schoolchildren, which indicate a TPOAb prevalence in the range of 3.4-4.6% (124,125).…”
Section: European Journal Of Endocrinologysupporting
confidence: 49%
“…The recent extensive Ab screening study in patients with T1DM has raised awareness of the association of T1DM with organ-specific autoimmunity [29]. The reported prevalence of thyroid autoimmunity in young T1DM patients ranges between 3% and 50% [10,[30][31][32][33], while it is 3.4%-7% in the general paediatric population [34,35]. The association of T1DM and AITD is highly dependent on age, sex and ethnicity [36].…”
Section: Discussionmentioning
confidence: 99%